Analysis of the Effect of Preset Surface Texture on Hard State Cutting - Zhao, Changlong; Ma, Chen; Ma, Zhenrong; Yang, Junbao; Li, Ming (Manufacturing Technology Journal, 2022)
In this paper, the electric discharge perforation technology is used to preset surface texture, which effectively suppresses the generation of large cutting forces in the hard cutting process, avoids the aggravation of tool wear, and improves the service life of the tool. Use CBN tools to hard-cut GCr15 hardened steel, design three-factor non-textured orthogonal cutting simulation and experiment about cutting depth, cutting speed, and feed rate, and use range, variance and signal-to-noise ratio methods to simulate and experiment data is analyzed to determine the best combination of cutting parameters and the degree of influence of each parameter on the cutting force generated in the hard cutting process. Use the best combination of cutting parameters to hard-cut GCr15 hardened steel with a preset surface texture, observe the tool wear, measure the cutting force, compare and analyze the results under the same cutting conditions without texture to verify the preset surface texture can effectively reduce tool wear and increase tool life.
Keywords: Hardened steel; Hard cutting; Orthogonal experiments; Cutting force; Preset texture; Tool wear